(untitled) (Bangladesh Agronomy Journal, 2021)
The field experiment was conducted at Agronomy Field of Patuakhali Science and Technology University, Patuakhali during the period from December 2019 to May 2020 to evaluate the effect of phosphorus (P0 = 0 kg P ha-1, P1 = 30 kg P ha-1, P2 = 60 kg P ha-1, P3 = 90 kg P ha-1) and boron (B0 = 0 kg B ha-1, B1 = 4 kg B ha-1, B2 = 6 kg B ha-1) and their combinations on nodulation and yield attributes of soybean. Number of nodules plant-1, number of pods plant-1, number of seeds pod, 1000-seed weight, seed yield, stover yield, biological yield and harvest index increased significantly up to 60 kg P ha-1. On the other hand, number of nodules plant-1, number pods plants-1, number of seeds pod-1, 1000-seed weight, seed yield, stover yield, biological yield and harvest index of soybean were enhanced significantly up to 4 kg B ha-1. The combination of 60 kg P ha-1 and 4 kg B ha-1 depicted the highest number of nodules (177.8), plant height (75.60 cm), number of pods plant-1 (92.72), number of seeds pod-1 (2.92), weight of 1000-seed (155.3 g) seed yield (1.91 t ha-1), stover yield (2.98 t ha-1), biological yield (4.89 t ha-1) and harvest index (39.06%). Thus, the combined application of 60 kg P ha-1 and 4 kg B ha-1 could be the optimum for getting maximum yield of soybean. Bangladesh Agron. J. 2020, 23(2): 127-133